BATS DIVERSITY IN THE NAPO-PUTUMAYO-AMAZONAS INTERFLUVIUM, PERU - RAMOS-RODRÍGUEZ, María Claudia (2020)
Bats are one of the most diverse groups of mammals in the neotropics and their functions as bioindicators underscore their importance. Thus, we studied population diversity, conservation status and threats at the Napo-Putumayo-Amazonas interfluvium, a sector that is still little explored in the Peruvian Amazon. We systematized studies from various sources focusing on the interfluvium. We found 53 species of bats, with the Phyllostomidae family and sub family Stenodermatinae sub family being the most represented. The species Artibeus lituratus, Artibeus obscurus, Lophostoma silvicolum, Phyllostomus elongatus, Rhynchonycteris naso and Sturnira tildae were widely recorded in Putumayo. There was greater diversity of frugivorous and insectivorous bats than bats of other eating habits. Diclidurus ingens is registered as a unique species, while Sturnira ludovici, Artibeus concolor, Cynomops greenhalli, Molossops neglectus and Platyrrhinus angustirostris are rare species. Given that these forests that are a source of life for many bat and other wildlife species, the urgent implementation of forest conservation projects that are compatible with the potentialities of the area are required.